The Impact of the Environment on the Production of Figurative Imagery in the Book (Khuraydat al-Qasr and Jaridat al-Asr) by the Author Imad al-Din al-Isbahani - Mohammed, Mahmood; Jassim, Saja (Al-Adab Journal, 2023)
The environment is the fundamental factor in the production of poetry and it is often said that a poet is a product of their environment. The environment is what creates a clear influence on poets. Poetic imagery is a reflection of reality; it is the environment’s impact on the poet. The poet paints their image using words infused with emotion and imagination. Poets often use similes, a technique adopted by pre-Islamic poets. We find that the pre-Islamic environment differs from the urban Abbasid environment, which altered the psyche of the poets. They employed clear and simple language in their poetic imagery. The imagery in the poetry of Khuraydah al-Qasr and Jaridah al-’Asr is marked by two main aspects: First, they followed the ancient poets’ tradition in employing imagery in praise, eulogy, and love poetry, often using long verses with multiple rhymes. Second, the Abbasid environment influenced poets to use beautiful imagery by describing palaces, gardens, and rivers. Most of these images were drawn from nature. Additionally, they introduced new barren imagery that had not been used by previous poets. Abbasid poets became more cultured due to cultural exchange with other peoples.